THE INTERACTION OF EARNING MANAGEMENT, CORPORATE SOCIAL RESPONSIBILITY AND CORPORATE GOVERNANCE (International Conference of Graduate School on Sustainability (ICGSS), 2018)
The interaction of earnings management and corporate social responsibility can have a positive impact on corporate governance. This interaction is analysis on the relationship among research variables. The purpose of this study is to analyse the relationship of earnings management, corporate social responsibility and corporate governance. The analysis method used is Pearson correlation analysis. The first independent variable, earnings management is measured by Friedlan's discretionary accrual model. Both independent variables of corporate social responsibility are measured based on the index of economic, social and environmental dimensions disclosure according to global reporting initiative standard (GRI standard). The three independent variables of corporate governance are measured based on corporate governance performance index (CGPI) scores. The findings of this study indicate that there is a significant correlation between earnings management and corporate governance. The existence of corporate governance directs and controls the company to perform earnings management, with the process of financial reporting and the intention of obtaining benefits for both managers and companies. The relationship of earnings management with corporate social responsibility is not significant. Corporate social responsibility is an on-going commitment, that companies not only achieve economic performance, but act ethically and contribute to society and the environment. This is in contrast to the more focused implementation of earnings management to benefit both managers and companies. The contribution of this research result is to be considered for companies and investors in the analysis of the strength relationship between earnings management, corporate social responsibility, and corporate governance.